The Capital Markets Union from the perspective of SMEs financing in the EU – expected benefits; constraints and risks - Waliszewski, Krzysztof (Unia rynków kapitałowych z perspektywy sektora MŚP w Unii Europejskiej – oczekiwane korzyści, zagrożenia i ryzyka, 2017)
The article is devoted to the project the Capital Markets Union (CMU) in the EU from the perspective of financing of the small medium enterprises. The EU Capital Markets Union is an important part of the Investment Plan for Europe of the Chairman Jean-Claude Juncker, and its goal is to effectively stimulate economic growth in the EU by increasing the availability of financing for businesses by the capital market and diversification sources of financing. European households are expected to be more active on the capital market by investing in financial instruments of this market. After the Brexit, there may be some difficulties in achieving the objectives since British capital market is the largest one in the EU. However, Brexit may also be a chance to keep the Union together and acceleration of the capital markets unification process. The author characterizes the problem of access to finance for enterprises from the SME sector in the EU. Then, he focuses on the financial markets and the structure and the effect of the Capital Markets Union in the EU. The article is based on a variety of sources, especially documents of the European Commission concerning the Capital Markets Union as well as literature on corporate finance and capital markets
Nauki o Finansach = Financial Sciences, 2017, Nr 2 (31), s. 102-116
Keywords: Capital Markets Union; Investment Plan for Europe; household savings; SME financing; market-based financial system model; unia rynków kapitałowych; Plan Inwestycyjny dla Europy; oszczędności gospdodarstw domowych; finansowanie MŚP; system finansowy oparty na finansowaniu rynkowym